2015 IEEE 23rd International Conference on Program Comprehension 2015
DOI: 10.1109/icpc.2015.30
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of the Forms of Java Reference Names

Abstract: Abstract-The readability of identifiers is a major factor of program comprehension and an aim of naming convention guidelines. Due to their semantic content, identifiers are also used in feature and bug location, among other software maintenance tasks. Looking at how names are used in practice may lead to insights on potential problems for comprehension and for programming support tools that process identifiers.Class and method names are already well represented in the literature. This paper presents an invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 17 publications
2
26
0
Order By: Relevance
“…The rule for 'local-variableboolean' inherits the typographic rules from 'local-variable'. The content field overrides the definition in the parent species and allows the use of noun phrases and verb phrases 4 , observed by Liblit et al [7], and of adjectival, adverbial and prepositional phrases, that we observed [13]. Ciphers are the only non-phrasal form of names permitted.…”
Section: Nominalmentioning
confidence: 79%
See 4 more Smart Citations
“…The rule for 'local-variableboolean' inherits the typographic rules from 'local-variable'. The content field overrides the definition in the parent species and allows the use of noun phrases and verb phrases 4 , observed by Liblit et al [7], and of adjectival, adverbial and prepositional phrases, that we observed [13]. Ciphers are the only non-phrasal form of names permitted.…”
Section: Nominalmentioning
confidence: 79%
“…Liblit et al's observations both increase the variety of phrasal forms expected, and require the division of species into boolean and non-boolean subspecies. Liblit et al 's metaphors have been used as a starting point for the extraction of information from names [5][6] and our previous work confirms the metaphors are widely used [13]. Further, recent research [7][5] [6] [14][13] [9] shows that developers use a range of phrasal structures wider than specified in EJS and JLS.…”
Section: B Naming Conventionsmentioning
confidence: 98%
See 3 more Smart Citations